Cloning and expression of cDNA encoding 28 kDa soluble protein (GRA2) tachyzoite of Toxoplasma gondii local isolate - Jarot Subandono, Jarot Subandono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Toxoplasma gondii is an intracellular parasite that causes toxoplasmosis and found in tropical countries. Toxoplasmosis is dangerous if suffered by pregnant woman or immunodeficiency patients. T. gondii has 28 kDa soluble protein from dense granule (GRA2) and among GRA proteins, GRA2 is probably the most immunogenic. Disruption of the GRA2 locus in T. gondii has resulted in decreasing of the parasite virulence in mice. Invasion of tachyzoite T. gondii into macrophages was also significantly inhibited by anti GRA2 antibody, therefore the availability of GRA2 protein is essential for development of protective vaccine.Objective: The aim of this research was to produce 28 kDa soluble protein (GRA2) by cloning and expression of cDNA encoding soluble protein tachyzoite of T. gondii local isolate.Methods: Total ribonucleic acid (RNA) and messenger RNA was isolated from tachyzoite of local T. gondii grown up in Balb/c mice. Messenger RNA was isolated from total RNA using polyATtract mRNA Isolation Systems and synthesis of cDNA using Universal RiboClone cDNA Synthesis Systems. Recombinants of pUC18 were transformed into E. co/i XL1-Blue by heat shock technique. Expression of recombinant protein was analysed by immunoblotting using polyclonal antibodies against soluble protein of T. gondii. Results: Two recombinant clones were isolated which expressed 28 kDa recombinant protein.Conclusion: Two recombinant clones were isolated. The immunoblotting result indicates that the recombinant expressed 28 kDa recombinant protein which hybridized with the antibody polyclonal against soluble protein of T. gondii and the proteins are possibly GRA2 proteins.Key words : Toxoplasma gondii - tachyzoite - cDNA - 28 kDa soluble protein.